Efficiency-wage hypothesis and the operational production pattern - Nadeem Naqvi; Carolin V. Schürg (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
An economy's production set is the collection of all net output vectors that the economy is capable of producing with a given technology and fixed quantities of primary factors of production. The boundary of this set is called the production possibility frontier or PPF. We show that, if the efficiency-wage hypothesis holds, a country's PPF, though conceptually valid, is an operationally irrelevant concept, because the economy never operates on the PPF, which is a view that ought to be appreciated in light of persistent unemployment in the new structure of economies of the post-21st-Century-crisis world.
Keywords: A20; D50; E23; F11; J23; J31; 330; general equilibrium; production set; production possibility frontier; efficiency wage; economic policy; labor market; Technische Effizienz; Allgemeines Gleichgewicht; Effizienzlohn; Arbeitslosigkeit; Wirtschaftspolitik; Theorie